A study of the methods of assay of acetaminophen in pharmaceutical dosage forms - Legaspi, Esther Jane A.
Spectrophotometric procedures for the assay of acetaminophen in pharmaceutical dosage forms are presented. Two methods for acetaminophen tablets are compared. The first involves the determination of the yellow derivative of acetaminophen after reaction with nitrous acid. The second involves preliminary column chromatography. Two methods for acetaminophen in liquid preparations (elixir and drops) are compared. The first involves a simple solvent extraction while the second includes a preliminary column chromatography. A method for separating and analyzing a mixture of acetaminophen, aspirin and caffeine is also reported.